(untitled) (Marketing Journal, 2026)
This article explores the role of digital marketing in modern society, with a focus on its influence on youth. The widespread availability of the internet and technology has increased digital literacy and fostered innovative thinking among young people. The article presents successful case studies of digital marketing campaigns and analyzes both the opportunities and challenges of the sector, particularly in the context of Uzbekistan. It also outlines future prospects and provides recommendations for empowe ring youth through digital marketing. № 1 -SON YANVA R, 202 6-YIL 102